Environmental characteristics and type 1 diabetes: students' perspectives on diabetes management in college - Malova, Ekaterina; Harrison, Tyler R. (Frontiers in Communication, 2023)
Type 1 diabetes is a chronic illness requiring immense lifestyle changes to reduce the chance of life-threatening complications, which can be especially challenging during the time of transition to college. Thus, this study applies a communication design perspective to qualitatively explore how students with type 1 diabetes interpret their experiences in college and what meanings they attribute to those experiences.Specifically, this study sheds light on physical and social environmental components affecting students' diabetes management. Four cultural themes emerged from the analysis: 1) Food environment, 2) Structural environment, 3) Academic life, and 4) Social life. The findings illustrate how food outlets and food accessibility, safe spaces for insulin injections, comfortable living spaces, availability of health support services, and diabetes-friendly classroom regulations constitute a higher-level environmental system affecting students' wellbeing.